Analisis Faktor Yang Berhubungan Dengan Pemeriksaan Inspeksi Visual Asam Asetat (IVA) - Fitria Lestari; Lilis Suryani; Akhmad Dwi Priyatno (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Cervical cancer is still a major health problem in women worldwide, early detection of cancer is carried out through the IVA examination method, but the achievement of early detection of cervical cancer in Musi Banyu Asin Regency is still below the national target, as well as the Ulak Paceh Public Health Center. This study aims to determine the factors that are associated with the Visual Acetate Inspection at the Ulak Paceh Health Center. The research design used is cross sectional, all women aged 30-50 years who live in the working area of the Ulak Paceh Health Center as many as 63 people taken as a total population. Data collection using a questionnaire conducted in May 2022. The results of statistical test analysis using the Chi-Square test showed that there was a relationship (p < 0.05) there was a relationship between age and IVA examination at WUS (p value = 0.047), there was a relationship between education and IVA examination at WUS (p value = 0.003), there is a relationship between access to information and IVA examination in WUS (p value = 0.000), there is a relationship between husband's support and IVA examination in WUS (p value = 0.000), there is a relationship between cadre support and IVA examination in WUS (p value = 0.000) The most dominant variable related to the IVA examination at WUS at the Ulak Paceh Health Center is the husband's support variable, with an OR value of 50.400. So the Puskesmas should provide information related to cervical cancer and early detection efforts through IVA examinations using electronic media, so that the information reaches the public